2019
DOI: 10.3389/fgene.2019.00980
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of the GASR Gene Family in Common Wheat (Triticum aestivum L.) and Characterization of TaGASR34, a Gene Associated With Seed Dormancy and Germination

Abstract: Seed dormancy and germination are important agronomic traits in wheat (Triticum aestivum L.) because they determine pre-harvest sprouting (PHS) resistance and thus affect grain production. These processes are regulated by Gibberellic Acid-Stimulated Regulator (GASR) genes. In this study, we identified 37 GASR genes in common wheat, which were designated TaGASR1-37. Moreover, we identified 40 pairs of paralogous genes, of which only one had a Ka/Ks value greater than 1, indicating that most TaGASR genes have un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 96 publications
2
52
0
Order By: Relevance
“…ZM895, ZY9507, YXM and SNTT are provided by Xianchun Xia from Chinese Academy of Agricultural Sciences.). The germination index was determined according to previous studies [46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ZM895, ZY9507, YXM and SNTT are provided by Xianchun Xia from Chinese Academy of Agricultural Sciences.). The germination index was determined according to previous studies [46].…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination and dormancy are important traits in wheat production. They determine PHS resistance, thus affecting the yield and quality of wheat [46]. Identi cation of candidate genes that control seed dormancy and germination may help to minimize yield and quality losses caused by PHS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in Arabidopsis thaliana by Herzog et al (1995) and then Roxrud et al (2007) have identified six new GASA genes, bringing the total number of GASA gene family members to 14 in A. thaliana (Herzog et al 1995;Roxrud et al 2007). Followingly, GASA genes have been studied on several plant species including Solanum tuberosum (Nahirñak et al 2016), Malus domestica (Fan et al 2017), Phyllostachys edulis (Hou et al 2018), Glycine max (Ahmad et al 2019), Oryza sativa (Muhammad et al 2019), Triticum aestivum L. (Cheng et al 2019), Vitis vinifera L. (Ahmad et al 2020), Sorghum bicolor (Filiz and Kurt 2020), Theobroma cacao (Faraji et al 2021) and cotton (Kaikai et al 2021) up to date. However, there is limited knowledge regarding the GASA genes in P. vulgaris genome.…”
Section: Introductionmentioning
confidence: 99%